PENINGKATAN KOMPETENSI UMKM WANDY SNACK DALAM SEGI PENGELOLAAN KEUANGAN - Dewi, Rike Tri Kumala Dewi; Sadikin, Jennifer; Pandova, Marta; Viola, Belicia; Matthew, Alexander; Effendi, Divania Lubherezky; Saputra, Willyam; Pratama, Davin Naldo (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
This community service aims to increase the knowledge in the financial management of SMEs (Small and Medium Enterprises), especially Wandy Snack as a small food and beverage business located in Kuningan District, West Java. The implementation of this Community Development aims to help Wandy Snack improve its sales performance and create an efficient bookkeeping system for better financial management. Through observation and business assistance, the three main problems were the lack of bookkeeping, unseparated business, personal finance, and inaccurate estimation of the cost of goods sold. The priority of the activities is to create an efficient bookkeeping system with financial journals. The second is to implement a petty cash system and encourage a business bank account to help separate business finances from household finances. Third, to train how to calculate the cost of goods sold accurately. The conclusion of this community service is that financial management improvement is crucial in determining the financial condition of a business, such that decision-making can be improved. However, the petty cash system is more brutal to be implemented as family finances come first for the business owner. — Pengabdian masyarakat ini bertujuan untuk menambah pengetahuan di bidang pengelolaan keuangan UMKM (Usaha Mikro, Kecil dan Menengah), khususnya untuk Wandy Snack sebagai usaha kecil makanan dan minuman yang berlokasi di Kabupaten Kuningan, Jawa Barat. Pelaksanaan Community Development ini bertujuan untuk membantu Wandy Snack meningkatkan kinerja penjualannya dan menciptakan sistem pembukuan yang efisien untuk pengelolaan keuangan yang lebih baik. Melalui pengamatan dan pendampingan usaha, ditemukan tiga masalah utama yaitu tidak adanya pembukuan, tidak terpisahnya keuangan usaha dan pribadi, serta perkiraan harga pokok penjualan yang tidak akurat. Prioritas pertama kegiatan adalah menciptakan sistem pembukuan yang efisien dengan jurnal keuangan. Kedua, menerapkan sistem kas kecil dan mendorong penggunaan rekening bank usaha untuk membantu memisahkan keuangan usaha dari keuangan rumah tangga. Ketiga, melakukan pelatihan literasi keuangan mengenai perhitungan harga pokok penjualan yang tepat. Kesimpulan dari pengabdian kepada masyarakat ini adalah perbaikan pengelolaan keuangan sangat penting dalam menentukan kondisi keuangan suatu usaha, sehingga dapat meningkatkan pengambilan keputusan. Namun, sistem kas kecil lebih sulit diterapkan karena keuangan keluarga adalah yang utama bagi mitra usaha.